Exploring polycaprolactone in tracheal surgery: A scoping review of in-vivo studies. (August 2019) - Chan, David S.; Fnais, Naif; Ibrahim, Iman; Daniel, Sam J.; Manoukian, John
Abstract: Introduction: Tracheal pathology can be life-threatening if not managed appropriately. There are still some surgical limitations today for certain pathologies, such as in severe tracheomalacia, or when long segments of trachea need to be resected. Poly(ε-caprolactone) (PCL) is a polymer that has recently gained popularity for its use in tracheal surgeries in animal models and in certain human pediatric cases in hopes of addressing these difficult situations. PCL can be 3D printed or manufactured through molds to create tracheal stents, splints, patches and even to reconstruct full circumferential tracheal defects. Objective: To perform a scoping review, and explore insights into the applications of PCL for tracheal surgeries in-vivo. Methods: A literature search in Embase, MEDLINE, and BIOSIS was performed to include all articles available prior to December 21, 2018 without any language restrictions. We included all original research that investigated the use of a PCL implant, stent, splint, scaffold, or graft in tracheal surgeries in-vivo. Assessment of all articles were performed by two independent authors prior to inclusion for analysis. Results: A total of 27 articles were included in the study. All articles were original research studies, primarily consisting of interventional studies (92.4%), there was also 2 case reports (7.4%). Articles were published in the last decade, publications range from 2009 to 2019. The most common animal model used for the tracheal surgeries were the New Zealand rabbits (n = 19, 70%). Two studies (7%) also described the use PCL in a total of 4 human cases. To investigate the PCL reconstructed airways, histology and bronchoscopy were the most commonly implemented methods of analysis in 88.9% and 70.4% respectively. Airway analysis was also done using imaging modalities including CT scan (n = 9, 33.3%), MRI (n = 2, 7.4%), X-ray (n = 1, 3.7%). 17 (62.9%) of the studies used 3D printing processes to create their PCL implants. Conclusions: Overall, this review demonstrates the feasibility of PCL in tracheal reconstruction and tracheal stenting/splinting. It highlights common trends and the limitations of the literature thus far on this topic.